Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/apa.12720
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent wheezing 36 months after bronchiolitis is associated with rhinovirus infections and blood eosinophilia

Abstract: Recurrent wheezing 36 months after infant bronchiolitis was associated with rhinoviruses and blood eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 30 publications
5
54
0
Order By: Relevance
“…Interestingly, our results add to previous findings that RV-A and RV-C wheezing illnesses contribute to the risk for recurrent wheezing (3, 5, 41, 42). In addition, Linsuwanon et al have earlier shown that RV-A and RV-C detected together with RSV were associated with recurrent wheezing (41, 43).…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, our results add to previous findings that RV-A and RV-C wheezing illnesses contribute to the risk for recurrent wheezing (3, 5, 41, 42). In addition, Linsuwanon et al have earlier shown that RV-A and RV-C detected together with RSV were associated with recurrent wheezing (41, 43).…”
Section: Discussionsupporting
confidence: 86%
“…This previously unreported finding suggests that recurrent wheezing after bronchiolitis depends on the type of virus the infants were found positive to, regardless of whether it was detected as a single or as a multiple virus. We previously reported a positive association between recurrent wheezing after bronchiolitis and hRV detection and in a later study a higher RSV‐RNA load . This issue merits clarification in a study with a larger number of cases and a longer follow‐up.…”
Section: Discussionmentioning
confidence: 86%
“…Around 40‐50% of infants hospitalized for bronchiolitis will have wheezing episodes in the first year of life. Although ample literature describes RSV, hRV, and the presence of higher blood eosinophil counts as factors predisposing to recurrent wheezing after bronchiolitis, the role of co‐infection is poorly understood. Enlarging current knowledge on the role of multiple viral detection in the clinical manifestation of bronchiolitis as well as in recurrent wheezing episodes would probably change the way we manage and follow‐up infants with acute bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…RV-induced severe bronchiolitis/early wheezing is a more robust marker of asthma risk than wheezing episodes caused by RSV or other viruses (Table I). 6,8,13,14,38,39 High-risk birth cohorts, which have included wheezing children with at least 1 atopic parent, have shown a close association between early-life RV-induced wheezing and school-age asthma. 6,9 The Childhood Origins of Asthma (COAST) study demonstrated that the risk for asthma by age 6 years was increased if the children had wheezing with RV (odds ratio [OR], 9.8) versus RSV (OR, 2.6) during the first 3 years, and furthermore, 90% of the children with RV-induced wheezing in the third year of life had asthma by age 6 years (OR, 26).…”
Section: Virus Characteristics Rvsmentioning
confidence: 99%
“…Acute wheezing illnesses with RV and respiratory syncytial virus (RSV) are early markers for recurrent wheezing. 6,[8][9][10][11][12][13][14] In addition, RV-induced wheezing episodes in infancy are a major risk factor for later asthma, especially in children with atopic features. Once asthma is established, exposure to allergens and RV infections are important triggers of asthma exacerbations in children.…”
mentioning
confidence: 99%